Diagnostic Accuracy of Three-Dimensional Endoanal Ultrasound for Anal Fistula: A Systematic Review and Meta-analysis - Jin Li; Shao-Na Chen; Yun-Yong Lin; Zhi-Min Zhu; Da-Lin Ye; Fei Chen; Shao-Dong Qiu (Turkish Journal of Gastroenterology, 2021)
Background: Anal fistula is a relatively common anorectal disease. An accurate assessment of the main anal fistula type and the anatomy of the internal opening before surgery is necessary to obtain the best surgical results. Whether three-dimensional endoanal ultrasound (3D-EAUS) should be used as the first-line diagnostic tool for anal fistula is still controversial. The purpose of this study is to conduct a meta-analysis of the published literature on 3D-EAUS and anal fistula, and compare the results of 3D-EAUS and surgery to evaluate the diagnostic value of 3D-EAUS for anal fistula. Methods: An online search of databases in English included PubMed, Embase, and Cochrane Library. After the diagnostic accuracy of 3D-EAUS of all anal fistula types was integrated, a single-group rate meta-analysis was performed; we analyzed 3D-EAUS separately for the diagnosis of different anal fistula types, and conducted a meta-analysis of test accuracy. The analysis combined sensitivity, specificity, and the respective 95% CI, to draw a summary receiver operating characteristic curve (SROC), and estimate the area under curve (AUC). Results: Based on the inclusion criteria, we selected 8 studies covering 1057 cases of anal fistula and 548 cases of internal opening. The meta-analysis data show that 3D-EAUS has a total accuracy rate of 91% (95% CI, 88-94%). It has high sensitivity and specificity for different anal fistula classifications. The SROC curves for anal fistula internal openings were plotted, and the AUC was calculated to be 0.86 (95% CI, 0.83-0.89). Conclusions: 3D-EAUS can be used as the first-line diagnostic tool for anal fistula, because it has a high diagnostic accuracy for most anal fistulas. However, due to the insufficient diagnostic accuracy of 3D-EAUS for complex fistulas, 3D-EAUS combined with MRI examination can be used to more accurately detect the secondary extension of complex fistulas, so as to describe the complete anatomy of the fistula in more detail. Cite this article as: Li J, Chen S, Lin Y, et al. Diagnostic accuracy of three-dimensional endoanal ultrasound for anal fistula: A systematic review and meta-analysis. Turk J Gastroenterol. 2021;32(11):913-922.